Application of Silica Adsorbent Rice Husk Ash-Activated Carbon in Refining Waste Cooking Oil - Gala, Donna Sumarni; Rahmanpiu, Rahmanpiu; Mulyana, Wa Ode (Universitas Pendidikan Mandalika, 2025)
A study has been conducted on “Application of Silica Adsorbent Rice Husk Ash-Activated Carbon in Refining Waste Cooking Oil”. This study aims to describe the comparison of silica-activated carbon composite in refining waste cooking oil and describe the optimum time of silica-activated carbon composite in refining waste cooking oil. The sample in this study was waste cooking oil from fried geprek chicken which was fried 5 times. While the adsorbent used was silica composite from rice husk ash and activated carbon. The method used in this study was adsorption. The stages in this study consisted of four stages, namely silica extraction from rice husk ash, making silica-activated carbon adsorbent composite, silica-activated carbon composite ratio (30:70; 40:60; 50:50; 60:40; and 70:30), and time variations, namely (30, 45, 60, 90) minutes. Silica extraction from rice husk ash using NaOH 12% solution obtained a silica content of 88%. The results of the study of silica-activated carbon composites in the purification of used cooking oil showed that the optimum silica-activated carbon composite adsorbent at a ratio of 60:40 grams and an optimum contact time of 30 minutes obtained a water content of 0.13%, free fatty acids of 0.23% and a peroxide number of 10.92 meq O2/Kg. The results of organoleptic tests with color, odor, and turbidity parameters obtained bright yellow results, less fried chicken odor, and not cloudy.